Long-Term Outdoor Cultivation of Nannochloropsis in California, Hawaii, and New Mexico - Alina A. Corcoran; Marcela Saracco Alvarez; Taryn Cornell; Isidora Echenique-Subiabre; Julia Gerber; Stephanie Getto; Ahlem Jebali; Heather Martinez; Jakob O. Nalley; Charles J. O’Kelly; Aidan Ryan; Jonathan B. Shurin; et al. (Data)
The project “Optimizing Selection Pressures and Pest Management to Maximize Cultivation Yield” (OSPREY, award #DE-EE08902) was undertaken to enhance the annual productivity, stability, and quality of algal production strains for biofuels and bioproducts. The foundation of this project was the year-round cultivation of a Nannochloropsis strain across three outdoor systems in California, Hawaii, and New Mexico. We aimed to leverage environmental selection pressures to drive strain improvement and use metagenomic techniques to inform pest management tools. The resulting dataset includes environmental and biological parameters from these cultivation campaigns, captured in a single CSV file. This dataset aims to serve a wide range of end users, from biologists to algal farmers, addressing the scarcity of publicly available data on algae cultivation. Further data releases will include 16S rRNA amplicon sequencing and shotgun sequencing datasets.